The Influence of Work Environment and Communication on Job Satisfaction - mutholib mutholib (International Journal Reglement & Society (IJRS), 2021)
The purpose of this research is to find out the influence of The Work environment and Communication on The Job Satisfaction of PDAM Tirtanadi North Sumatra Province. Data collection method in this research through field analysis techniques or surveys with the spread of questionnaires and interviews. variable data measurement is done using a likert scale through the respondent's answer score between 1-5, where the score 1 indicates a strongly agreed statement while a score of 5 indicates a strongly disagreed statement. The samples taken in this study were employees of PDAM Tirtanadi North Sumatra Province, which numbered 72 employees. Data analysis techniques used to determine the influence on related variables are using classic assumption test techniques, multiple linear regressions, T (partial) tests, F (simultaneous) tests, and determination coefficients with the help of SPSS (Statistical Product and sevice solution) software v. 16. The results of the analysis showed a positive and significant influence between variable X1 (Work Environment) to variable Y (Job Satisfaction) shown at a calculated t value of 2,296 with a probability of sig 0.018 smaller than α = 0.05. Variable X2 (Communication) against variable Y (Job Satisfaction) shown at calculated t value 2293 with a probability of sig 0.011 less than α = 0.05. This means that the Work and Communication Environment significantly has an influence on Job SatisfactionPDAM Tirtanadi North Sumatra Province.